Genetic influence on blood pressure and underlying hemodynamics measured at rest and during stress - Wu, Ting (2013)
OBJECTIVE: This study examined genetic and environmental contributions to the individual differences in blood pressure (BP) levels and underlying hemodynamic characteristics at rest and during mental challenge tasks in a large twin cohort of youth. Including both European American (EA) and African American (AA) twins further allowed examination of potential ethnic differences. METHODS: We studied CVR to two stressors (car driving simulation and a social stressor interview) in 308 EA and 223 AA twin pairs including monozygotic twin pairs and same-sex as well as opposite-sex dizygotic twin pairs (mean [SD] age: 14.7 [3.1]). Variables included systolic and diastolic BP, heart rate (HR), stroke volume, cardiac output and total peripheral resistance. RESULTS: Heritability indices for levels at rest and during stress were high (31% – 73%) and comparable between ethnic groups. A common genetic factor accounted for both resting and stress levels explaining 23% to 58% of the total variance. The increases in heritability indices for BP and HR from rest to stress are mostly explained by newly emerging genetic influences on the added stress component. Indices for hemodynamic variables remained stable from rest to stress owing to a simultaneous decrease in genetic and environmental variances. CONCLUSIONS: Cardiovascular measures obtained during rest and stress show substantial heritability that is comparable between individuals of African and European descent. Most of the variance in both resting and stress levels is explained by common genetic factors, although other genetic factors that only contribute to cardiovascular levels during stress are also important.